1998
DOI: 10.1073/pnas.95.16.9313
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative mechanism of action of cryptophycin-52: Kinetic stabilization of microtubule dynamics by high-affinity binding to microtubule ends

Abstract: Cryptophycin-52 (LY355703) is a new synthetic member of the cryptophycin family of antimitotic antitumor agents that is currently undergoing clinical evaluation. At high concentrations (>10 times the IC 50 ), cryptophycin-52 blocked HeLa cell proliferation at mitosis by depolymerizing spindle microtubules and disrupting chromosome organization. However, low concentrations of cryptophycin-52 inhibited cell proliferation at mitosis (IC 50 ‫؍‬ 11 pM) without significantly altering spindle microtubule mass or orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 27 publications
5
106
1
Order By: Relevance
“…Microtubules are unusual receptors for drugs in that an individual microtubule contains ϳ1690 tubulin dimers/m of length and, thus, very large numbers of binding sites. In addition, occupancy of just a few sites on an individual microtubule exerts powerful suppression of dynamics (17,25). The two drugs did exert different effects on the length-based catastrophe frequency.…”
Section: Synergistic Inhibition Of Microtubule Dynamic Instability Bymentioning
confidence: 99%
“…Microtubules are unusual receptors for drugs in that an individual microtubule contains ϳ1690 tubulin dimers/m of length and, thus, very large numbers of binding sites. In addition, occupancy of just a few sites on an individual microtubule exerts powerful suppression of dynamics (17,25). The two drugs did exert different effects on the length-based catastrophe frequency.…”
Section: Synergistic Inhibition Of Microtubule Dynamic Instability Bymentioning
confidence: 99%
“…Many microtubule-targeted drugs, including vinblastine, colchicine, cryptophycin 52, and paclitaxel, can bind with relatively high affinity directly to microtubules, either to their ends, as with the first three drugs, or along their lengths, as with paclitaxel (10,23,32,41,42). Many drugs that bind directly to microtubules can stabilize the microtubule against shortening and significantly alter the catastrophe and rescue frequencies.…”
Section: Mechanism Of Action Of E7389mentioning
confidence: 99%
“…7 -8 For Cryptophycin A, the ratio of cryptophycin concentration to the concentration of tubulin was calculated to be approximately 1:400. 8 Cryptophycin-52 is even more potent, having a ratio of approximately 1:2,500, 7 making it the most potent stabilizer of microtubulin dynamics currently known.…”
mentioning
confidence: 99%
“…Within the past year, it was discovered that Cryptophycin A and Cryptophycin-52 interact with tubulin to stabilize the dynamics at picomolar concentrations, without altering the microtubule content or organization. 7,8 Earlier, it was known that micromolar concentrations of cryptophycin inhibited tubulin polymerization 1 ,9 by targeting tubulin, altering the microtubule/tubulin equilibrium, and causing it to depolymerize and form aggregates within cells. 9,10 More recent studies have indicated that the mechanism of action may involve the interaction of cryptophycin at the microtubule ends.…”
mentioning
confidence: 99%
See 1 more Smart Citation